FOREIGN EXPERIENCE OF LEGAL REGULATION OF TRADE SECRETS AND KHOW-HOW - Smirnov, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of this article is to consider the peculiarities of the legal regulation of trade secrets and know-how (confidential information) by foreign legislation. This article analyzes the provisions of the laws of individual countries and known doctrines and concepts to determine the basic premises of the approach to understanding trade secrets and know-how (confidential information) in view of the existing theories there. This was done on the example of countries with a continental (pandect) legal system. The methodological basis of the research is general scientific and special methods of cognition. The use of these methods made it possible to describe problems related to the peculiarities of legal regulation of trade secrets and know-how (confidential information) by foreign legislation. Results: the violation of commercial secrets and know-how (confidential information) is considered by the international legislation of foreign countries as a fact of unfair competition. At the same time, it should be noted that the laws on unfair competition of the countries of the continental (pandect) legal system are based on the theory of confidentiality (actual monopoly). Discussion: as is known, the current legislation of Ukraine, and in particular the Civil Code of Ukraine, is built on the model of the German (pandect) legal system. Therefore, the author believes that the foreign experience of countries with a continental (pandemic) legal system is of particular importance for the formation of national legislation on trade secrets and know-how (confidential information).